MENGUATKAN MODERASI BERAGAMA SISWA BERBASIS LOCAL WISDOM DI LINGKUNGAN MADRASAH TSANAWIYAH - Hidayat, Imam; Hamid Samiaji, Mukhamad (Jurnal Nusantara Raya, 2023)
This research is based on the phenomenon of intolerant attitudes that occur in students. This raises concerns from teachers, educational institutions, to the government in responding to this intolerant attitude. Meanwhile, the presence of the Decree of the Minister of Religious Affairs Number 184 of 2019 as a guideline for curriculum implementation in madrassas answered these concerns by inserting strengthening religious moderation based on local wisdom in madrasas. The results of this study show that the scheme to strengthen religious moderation based on local wisdom for students in the tsanawiyah madrasah environment is through local wisdom studies, religious education development, character building, parental involvement, student empowerment, evaluation and monitoring. This scheme can be applied in a habituation model whose implementation can be done with routine, incidental, and exemplary activities. These methods become cultural products of students, which can be used and applied in community life (empowerment). Strengthening religious moderation based on local wisdom also has an impact on students' culture of moderate reason.